Corporate social responsibility in the digital age - Adi, Ana.; Grigore, Georgiana; Crowther, David (Bingley, U.K. : Emerald, 2015)
Over the past half century, corporate social responsibility has become an important concept in management, marketing and communication literature. In the past twenty years a visible shift has been made into what was written about CSR: a move away from the financial benefits derived from such activities towards reputational impact, stakeholder relationships and communication with a wide range of audiences being note. With social and digital media reshaping the way in which business is conducted, and with the number of companies embracing the new social medium for their marketing and communication programmers, this book re-examines CSR practices from a digital perspective. In doing so, it revisits some of the theoretical discussions about CSR while inquiring whether and how CSR can be applied online. This book examines key conceptual insights about corporate social responsibility and digital and social media, and explores best practices for online CSR. In this way, the volume explores the impact and influence of the new ãaĉsocialãa on responsibility and its feasibility, measurability and success in a boundary-less world.
Introduction to corporate social responsibility in the digital age -- Schrodinger's cat in Facebook : a Lacanian perspective / David Crowther, Shahla Seifi -- The rhetorical citizenship of corporations in the digital age / Elisabeth Hoff-Clausen, ¢yvind Ihlen -- Dear brands of the world : CSR and the social media / Massimiliano Di Bitetto, Salvatore Pettineo, Paolo D'Anselmi -- Classifying social causes derived from the communication of CSR initiatives online : a theoretical and practical approach / Mihai Ioan Rosca, Andrei Claudiu Sarau, Andreea-Angela Vontea -- How activists shape CSR : insights from internet contagion and contingency theories / W. Timothy Coombs, Sherry J. Holladay -- CSR and new battle lines in online PR war : a case study of the energy sector and its discontents / David McQueen -- Two minute drill : video games and social media to advance CSR / W. Timothy Coombs, Sherry J. Holladay -- Communicating CSR on social media : the case of Pfizer's social media communications in Europe / Ana Adi, Georgiana Grigore -- Using social media for CSR Communication and engaging stakeholders / Imran Ali, Ana Jimâenez-Zarco, Marta Bicho -- A synoptic research overview of CSR amongst Romanian managers / Dumitru Bortun -- CSR and social media : could online repositories become regulatory tools for CSR related activities reporting? / Camelia Crisan, Alexandra Zbuchea -- Digital reflections of pharmaceutical companies and their CSR communication strategies / Georgiana Grigore, Ana Adi, Anastasios Theofilou -- CSR Online and in real terms : a critical analysis of controversial sectors in Hungary / Gyèorgy Pataki, Richâard Szâantâo, Râeka Matolay.
Includes index.
Print version record
Keywords: Business & Economics -- Business Ethics; Business ethics; Social responsibility of business; Business ethics